1978
DOI: 10.1111/j.1600-0714.1978.tb01612.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional deficiencies in recurrent aphthae

Abstract: A series of 330 patients with recurrent aphthae was screened for deficiencies of iron, folate and vitamin B|2. In 47 patients (14.2 %) such deficiencies were found; 23 were deficient in iron, seven in folic acid, six in vitamin B|2 and in addition 11 patients had combined deficiencies.Clinical examination of the aphthae was not helpful in identifying individual patients with a nutritional deficiency although patients with an associated glossitis or angular cheilitis were more likely to suffer from such deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
1
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 6 publications
1
37
1
5
Order By: Relevance
“…In the research conducted by Olson et al (13), no significant difference was found between hematological parameters in patients with aphthous and healthy people, and these results were inconsistent with those of the current research, which examined these parameters in patients and healthy controls. Since some reports indicated that about 18% of patients with recurrent aphthous stomatitis are diagnosed with deficiencies in vitamin B12, folate, or iron, the hypothesized relationship between recurrent aphthous stomatitis and hematological disorders has been discussed (6,14). This suggests the importance of blood examination in diagnosis and treatment of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the research conducted by Olson et al (13), no significant difference was found between hematological parameters in patients with aphthous and healthy people, and these results were inconsistent with those of the current research, which examined these parameters in patients and healthy controls. Since some reports indicated that about 18% of patients with recurrent aphthous stomatitis are diagnosed with deficiencies in vitamin B12, folate, or iron, the hypothesized relationship between recurrent aphthous stomatitis and hematological disorders has been discussed (6,14). This suggests the importance of blood examination in diagnosis and treatment of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The research conducted by Wary et al showed that topical treatments led to improvement until the treatment process continued (14), however, after the end, aphthous ulcers reappeared. Also, these treatments could not reduce the intervals and recurrence of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…5,8,11,[15][16][17][18] Iron, vitamin B12 and folic acid deficiencies were reported as predisposing factors in RAS in several studies. 4,5,8,10,11,16,18 Porter et al 18 have determined the frequency of anaemia and/or HD in RAS. They indicated that 11.6% of RAS patients had low iron storage when compared with 4.9% of control subjects and also indicated that neither patients nor control subjects had anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] The role and prevalence of HD such as iron, folic acid and vitamin B12 deficiencies in the aetiopathogenesis of RAS are not well known and many conflicting results have been reported in the literature. 4,5,[7][8][9][10] Wray et al 8,11 reported increased incidence of HD in RAS patients and suggested haematological screening in such patients. While many researchers supported this relationship, 5,9-13 conflicting studies exist as well.…”
mentioning
confidence: 99%
“…O novo conhecimento que a biologia molecular tem trazido a este campo vem também nos ajudando a compreender os vários fatores modificadores do comportamento das UAR que foram sendo observados pelos clínicos ao longo da história das UAR (Ship, 1972;Stanley, 1972;Miller;Ship, 1977;Wray et al, 1978;Wray et al, 1981;Woo, Sonis, 1996;Shotts et al, 1999;Tuzun et al, 2000;Boulinguez et al, 2000;Casiglia, 2002;Scully et al, 2003;Natah et al, 2004;Scully, Felix, 2005;Scully, Porter, 2008;Tappuni et al, 2013). Barros et al (2010) propuseram um modelo para a explicação dos eventos imunológicos que culminam na lesão de UAR, este está baseado no desequilíbrio das respostas Th1/Th2, a disfunção da barreira epitelial causada por alterações na função da via do receptor TLR2 em conjunto com uma redução da tolerância imunológica.…”
Section: Resultsunclassified